The effect of plyometric training and motivation on the explosive power of leg muscles of extracurricular volleyball students of SMPN 2 Bantan - Firza Jurdila; Bafirman HB; Muhamad Sazeli Rifki; Masrun Masrun; Fiky Zarya (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2023)
This study aims to see the difference in the effect of plyometric training and motivation on the explosive power of the limb muscles of volleyball extracurricular students of SMPN 2 Bantan. experimental research design, This type of research is quasi-experimental, the population of this study is all extracurricular volleyball students of SMPN 2 Bantan totaling 60 people, the sample in this study is 32 students, and The sampling technique uses the verdict formula which is 27%. This sampling technique was carried out on a population of 60 people. The instrument used is a leg muscle explosive power test using vertical jump and a Likert scale questionnaire. The data obtained were analyzed with a two-track ANOVA and continued with the Tuckey test. Based on the results of data analysis show that: 1) Overall, there is a difference in the effect between plyometric Quick Leap training and plyometric Depth jump training on the explosive power of leg muscles of volleyball extracurricular students of SMP Negeri 2 Bantan. 2) There is an interaction between the Quick Leap plyometric training approach and the Depth jump plyometric training approach with motivation for the leg muscle explosive power of SMPN 2 Bantan volleyball extracurricular students. 3) In the plyometric Quick Leap exercise, high motivation is better than the Depth jump plyometric training approach to the explosive power of the leg muscles of SMPN 2 Bantan volleyball extracurricular students. 4) In the plyometric exercise, low motivation depth jump is better than the Quick Leap plyometric training approach to the explosive power of the limb muscles of SMPN 2 Bantan volleyball extracurricular students. Based on the results of this study, it can be concluded that plyometric Quick Leap and Depth Jump exercises have different influences on increasing the explosive power of the limb muscles of SMPN 2 Bantan volleyball extracurricular students, especially when considering the level of student motivation.